Stem Cells in the Myelodysplastic Syndromes - Zhan, Di; Park, Christopher Y. (Frontiers in Aging, 2021)
The myelodysplastic syndromes (MDS) represent a group of clonal disorders characterized by ineffective hematopoiesis, resulting in peripheral cytopenias and frequent transformation to acute myeloid leukemia (AML). We and others have demonstrated that MDS arises in, and is propagated by malignant stem cells (MDS-SCs), that arise due to the sequential acquisition of genetic and epigenetic alterations in normal hematopoietic stem cells (HSCs). This review focuses on recent advancements in the cellular and molecular characterization of MDS-SCs, as well as their role in mediating MDS clinical outcomes. In addition to discussing the cell surface proteins aberrantly upregulated on MDS-SCs that have allowed the identification and prospective isolation of MDS-SCs, we will discuss the recurrent cytogenetic abnormalities and genetic mutations present in MDS-SCs and their roles in initiating disease, including recent studies demonstrating patterns of clonal evolution and disease progression from pre-malignant HSCs to MDS-SCs. We also will discuss the pathways that have been described as drivers or promoters of disease, including hyperactivated innate immune signaling, and how the identification of these alterations in MDS-SC have led to investigations of novel therapeutic strategies to treat MDS. It is important to note that despite our increasing understanding of the pathogenesis of MDS, the molecular mechanisms that drive responses to therapy remain poorly understood, especially the mechanisms that underlie and distinguish hematologic improvement from reductions in blast burden. Ultimately, such distinctions will be required in order to determine the shared and/or unique molecular mechanisms that drive ineffective hematopoiesis, MDS-SC maintenance, and leukemic transformation.